2022
DOI: 10.3390/molecules27175412
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination and Pharmacokinetics Study of Three Triterpenes from Sanguisorba officinalis L. in Rats by UHPLC–MS/MS

Abstract: A selective and rapid ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) method was established and validated for the determination of ziyuglycoside I, 3β,19α-dihydroxyurs-12-en-28-oic-acid 28-β-d-glucopyranosyl ester, and pomolic acid in rats after the oral administration of ziyuglycoside I, 3β,19α-dihydroxyurs-12-en-28-oic-acid 28-β-d-glucopyranosyl ester, pomolic acid, and Sanguisorba officinalis L. extract. The separation was carried out on an ACQUITY UPLC®HSS T3 column (2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The sample processing methods and mobile phase were optimized to improve peak shape, stabilize retention time, increase the signal response of analytes, and shorten run time [15][16][17]. In this study, the influence of different mobile phase combinations (methanol-water, acetonitrile-water) and added buffers (formic acid, acetic acid, ammonium formate, and ammonium acetate) on the chromatographic behavior of the target compound was investigated.…”
Section: Uhplc-ms/ms Methods Optimizationmentioning
confidence: 99%
“…The sample processing methods and mobile phase were optimized to improve peak shape, stabilize retention time, increase the signal response of analytes, and shorten run time [15][16][17]. In this study, the influence of different mobile phase combinations (methanol-water, acetonitrile-water) and added buffers (formic acid, acetic acid, ammonium formate, and ammonium acetate) on the chromatographic behavior of the target compound was investigated.…”
Section: Uhplc-ms/ms Methods Optimizationmentioning
confidence: 99%
“…Subsequently, we subjected the three onoceranoid triterpenes to pharmacokinetic prediction, including absorption, distribution, metabolism, and excretion properties. These pharmacokinetic criteria are essential in drug development, as they provide insights into the behavior of compounds in the body and their potential efficacy [43]. Additionally, the toxicity properties of the onoceranoid triterpenes were assessed, which is crucial for evaluating their safety and possible adverse effects [44].…”
Section: Prediction Of Drug-likenessmentioning
confidence: 99%
“…Ziyuglycoside I and ziyuglycoside II, isolated from Sanguisorba ofcinalis L., are the important active components of Sanguisorba ofcinalis L., which have excellent pharmacological efects. Many studies have shown that saponins extracted from Sanguisorba ofcinalis L. have antioxidant and anticancer efects [7][8][9]. Among other things, ziyuglycoside I could prevent the formation of collagen fbers, efectively promote the production of type I collagen, and reduce the generation of skin wrinkles, which could be used in the synthesis of beauty and skin care products [7,10].…”
Section: Introductionmentioning
confidence: 99%